Violent behavior and the COVID-19 lockdowns: a nationwide register-based study - Pisl, Vojtech; Vevera, Jan; Holas, Jakub; Volavka, Jan (CNS spectrums, 2023)
OBJECTIVES: The primary aim was to test the hypothesis that physical interpersonal violence is decreased during the lockdown period in comparison with comparable control periods. The secondary aims were to explore the effects of gender and alcohol consumption on the violence during the lockdown. METHODS: Nationwide records of hospitalizations secondary to an assault were analyzed using quasipoisson regression. Assault rates in two lockdown periods, defined as a national emergency state, were compared to baseline data between 2017 and 2020, controlling for seasonal fluctuations and pandemic-related effects other than lockdown. To validate the findings on independent data, differences between lockdown and baseline in Police records of violent criminality between 2017 and 2021 were examined using one-way ANOVA. RESULTS: The rates of hospitalizations secondary to an assault decreased substantially during lockdowns (IRR = .43; P < .001) and the duration of lockdown did not affect assault rates (P = .07). The decrease in assault rates was more pronounced in males than females (IRR = .77; P < .05) and was weakened in patients with history of alcohol abuse (IRR = 1.83; P < .001). Violent crime rate decreased by 19% during the lockdowns compared to prepandemic baseline (P < .001). CONCLUSION: We found that physical interpersonal violence decreased during the COVID-19 lockdown periods. The reduction is significantly greater in males. Emerging evidence suggests an increased risk of alcohol use and intoxication during the lockdowns. Violent crime rate decreased during the lockdown.
Keywords: Female; Quarantine; lidé středního věku; mužské pohlaví; Humans; dospělí; Sex Factors; hospitalizace; registrace; lidé; Middle Aged; násilí; sexuální faktory; senioři; karanténa; ženské pohlaví; Hospitalization; Alcohol Drinking; Violence; Aged; pití alkoholu; Adult; Registries; Male; COVID-19